Toward the Commercialization of Carbon Nanotube Field Effect Transistor Biosensors - Zhongyu Li; Mengmeng Xiao; Chuanhong Jin; Zhiyong Zhang (Biosensors, 2023)
The development of biosensors based on field-effect transistors (FETs) using atomically thick carbon nanotubes (CNTs) as a channel material has the potential to revolutionize the related field due to their small size, high sensitivity, label-free detection, and real-time monitoring capabilities. Despite extensive research efforts to improve the sensitivity, selectivity, and practicality of CNT FET-based biosensors, their commercialization has not yet been achieved due to the non-uniform and unstable device performance, difficulties in their fabrication, the immaturity of sensor packaging processes, and a lack of reliable modification methods. This review article focuses on the practical applications of CNT-based FET biosensors for the detection of ultra-low concentrations of biologically relevant molecules. We discuss the various factors that affect the sensors’ performance in terms of materials, device architecture, and sensor packaging, highlighting the need for a robust commercial process that prioritizes product performance. Additionally, we review recent advances in the application of CNT FET biosensors for the ultra-sensitive detection of various biomarkers. Finally, we examine the key obstacles that currently hinder the large-scale deployment of these biosensors, aiming to identify the challenges that must be addressed for the future industrialization of CNT FET sensors.